Application of Medical Adhesive in Emergency Treatment of Head and Face Injury. Issue 3 (May 2021) - Wang, Chaochao; Zhang, Li; Chen, Muhu; Zhong, Wu
Abstract : Purpose: The aim of this study was to analyze the application effect of medical adhesive in emergency surgical scalp and facial skin treatment. To explore the better application of medical adhesive in emergency work Methods: A total of 180 patients with scalp and facial skin laceration admitted to the emergency department of the Affiliated Hospital of Southwest Medical University from August 2018 to August 2019 were selected. The patients were divided into the control group (n = 70) and the treatment group (n = 110) using the random number table method. The control group was treated with debridement, local anesthesia, and suture technique without medical adhesive, whereas the treatment group was treated with medical adhesive after debridement without local anesthesia. The operation time, pain degree, total cost, and satisfaction of the 2 groups were compared. Results: The operation time in treatment group was shorter than that in control group (12.0 ± 2.6 minutes versus 17.7 ± 2.5 minutes, P  < 0. 05), and the visual simulation score (VAS) of treatment group were lower than that in control group (2.45 ± 1.63 versus 5.66 ± 1.65, P  < 0. 05), and the total cost in treatment group was higher than that in control group (¥906.6 ± 69.0 versus ¥329.8 ± 76.4, P  < 0. 05). In control group 17 not satisfiedpatients, satisfied 37 patients, and 16 patients felt excellent; in treatment group, there are 7 not satisfiedpatients, 21 satisfied patients, and 82 felt excellent. Patients' satisfaction was compared between the 2 groups, the difference was statistically significant ( P  < 0.05). Conclusions: The results suggest that Medical adhesive used in scalp skin trauma and facial wounds had the advantages of shorter operation time, less pain, and higher postoperative satisfaction of patients, but higher cost than conventional suture. Medical adhesive has obvious advantages and high feasibility in the treatment of scalp and facial skin wounds. Abstract : Supplemental Digital Content is available in the text